Effect of Na2SO4 and Fe2(SO4)3 on the oxidation behaviour of AISI-303 Alloy at 900° - Muhammed Misbahul, Amin (Africa Journals Online, 2009)
Link to publisher's homepage at http://ajol.info/index.php/bcse